Economic Impacts of Educational Tourism in Jordan - Alhasan, Lana; Alzboun, Nidal M.; Khawaldah, Hamzah A. (Jordan Journal of Social Sciences, 2023)
The aim of this study is to identify the economic effects of the educational tourism in Jordan. Behavioral and descriptive and analytical statistical approaches were used. The results of the study were based on a questionnaire, which was designed for collecting the required data and was distributed to a random sample of (1000) international students, who study at the (the University of Jordan, Mu'tah University, Al-Ahliyya Amman University, Philadelphia University, Isra University and The World Islamic Science University). 844 questionnares were analyzed using SPSS. The results indicated that the highest percentage of international students were at the University of Jordan, and their field of study usually is in medicine and health majors, and the largest number of international students were Iraqi students. The economic effects were represented in spending rates for international students that include spending on: university fees; food and drink; communications; housing; books and stationery; and transportation. According to the survey, the most common obstacle that international students faced during their stay in Jordan were: the high costs of accommodations in tourists places; the high cost of food and drinks; the cost of tickets for some tourist places. The results also indicate that there is also a statistically significant effect at (α ≤ 0.05) for gender variable on the economic variables: tuition fees rate; books and students supplies; and the costs of tourist trips. In addition, there was no statistically significant effects at (α ≤ 0.05) for gender variable on of the economic variables such as: expenditure on housing; transportation; communications; and food and drinks. There is also a statistically significant effect at (α ≤ 0.05) for nationality, university type, and specialization variables on the following economic variables: tuition fees rate; housing; books and students’ supplies; transportation; food and drink; and the costs of tourist trips. The study concluded with several recommendations and the most important is the necessity to propose coordination between the Ministry of Higher Education and Scientific Research and the Ministry of Tourism and Antiquities in general, and Jordanian universities in particular; to create promotional programs for tourist sites targeting international students.